Living With the Other The Ethic of Inner Retreat - Sagi, Avi (Contributions to Phenomenology, In Cooperation with The Center for Advanced Research in Phenomenology,, 2018)
The book grapples with one of the most difficult questions confronting the contemporary world: the problem of the other, which includes ethical, political, and metaphysical aspects. A widespread approach in the history of the discourse on the other, systematically formulated by Emmanuel Levinas and his followers, has invested this term with an almost mythical quality-the other is everybody else but never a specific person, an abstraction of historical human existence. This book offers an alternative view, turning the other into a real being, through a carefully described process involving two dimensions referred to as the ethic of loyalty to the visible and the ethic of inner retreat. Tracing the course of this process in life and in literature, the book presents a broad and lucid picture intriguing to philosophers and also accessible to readers concerned with questions touching on the meaning of life, ethics, and politics, and particularly relevant to the burning issues surrounding attitudes to immigrants as others and to the relationship with God, the ultimate other. .